MÉTODOS ALTERNATIVOS PARA ESTIMAÇÃO DE ESTADO EM SISTEMAS DE ENERGIA ELÉTRICA - Frazão, Rodrigo José Albuquerque (2012)
The state estimation process applied to electric power systems aims to provide a trustworthy ―image‖, coherent and complete of the system operation, allowing an efficient monitoring. The state estimation is one of the most important functions of energy management systems. In this work, will be proposed alternative methods of state estimation for electric power systems in the levels of transmission, subtransmission and distribution. For transmission systems are proposed two hybrid methods considering the insertion of conventional measurements combined with phasor measurements based on phasor measurement unit (PMU). To estimate the state in subtransmission systems is proposed an alternative method which, in occurrence of failures in active and/or reactive meters in the substations, uses a load forecasting model based on criteria similar days and application of artificial neural networks. This process of load forecasting is used as a generator of pseudo measurements in state estimation problem, which takes place through the propagation of phasor measurements provided by a PMU placed in the boundary busbar. For the distribution system state estimation the proposed method uses the mathematical method of weighted least squares with equality constraints by modifying the set of measurements and the state variables. It is also proposed a methodology evaluation of the PMUs measurement channel availability for observability analysis. The application of the proposed methods to test systems shows that the results are satisfactory.